Meat intake among adults: a population-based study in the city of Campinas, Brazil. A cross-sectional study - Avila, Jaqueline Contrera; Luz, Verônica Gronau; Assumpção, Daniela de; Fisberg, Regina Mara; Barros, Marilisa Berti de Azevedo (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: Meat is a food with high nutritional density that has significant participation in the Brazilian diet. However, in excess it can cause harm to health. The aim of this study was to analyze the meat intake (g/day) among adults according to sociodemographic, behavioral and health situation characteristics, and to assess the types of meat most consumed. DESIGN AND SETTING: Cross-sectional population-based study conducted in the city of Campinas, São Paulo, Brazil, in 2008 and 2009. METHODS: Two-stage cluster sampling was used. The analysis included 948 adults between 20 and 59 years, who were participants in the Campinas Health Survey. Meat intake was assessed using 24-hour dietary recall. RESULTS: The mean meat intake adjusted for sex and age was 182.3 g (95% CI: 170.6-193.9 g), with signifi- cantly lower intake among women, individuals aged 50 years or over, those with the presence of two or more self-reported chronic diseases and those with three or more health complaints. Higher meat intake was found in segments with intermediate monthly family income (between 1 and 3 minimum wages), those with 16 or more appliances per household and those who consumed soft drinks seven days a week. Beef was consumed most frequently (44%) among the meats in the diet, followed by poultry, fish and pork. CONCLUSION: The data from this study reveal high meat intake in the population of Campinas and iden- tify the segments that need to be prioritized for strategies directed towards appropriate meat intake.